Tennis and scoliosis: an approach without prejudice - Lisi, R.; Cigni, S. (International Journal of Racket Sports Science, 2023)
This contribution intends to offer a concise and exhaustive overview of the scientific production on the topic, as well as to provide researchers with theoretical reflections, scientific hypotheses and what can be deduced from the personal baggage of experience in the field, albeit limited. All permeated by the hope that future epidemiological investigations will be conducted, compared to the past, with greater methodological rigor and with a more coherent and incisive modus operandi. It is unfortunately undeniable that until today the medical sciences have not been able or able to deal with the topic except in a fragmentary manner and with sometimes questionable criteria. The consequences? Few valid studies and too many hasty judgments. Judgments that have not infrequently been affected by a certain habit of our time: a sterile prevalence of discussions and abstractions of a physiopathological type, without the necessary attention to "evidence-based medicine" (Lisi, 2018).